Women’s Role in Tourism Development (Study Case: Tourism Awareness Group Galo-Galo Island, Morotai) - Noviyanti Soleman (IAIN TERNATE, 2020)
Morotai was set as the special economic zones have potential of geo-economy and geo-strategy to boosting the economic.Galo Galo Island is one of the many islands in Morotai Regency with good tourism potential. In Galo Galo tourism development, there are local communities involved through Tourism Awareness Group. The development is would be better to involve women, especially the case of Galo Galo Island has women population almost similar to men population. This is show how important the women’s role in the tourism development of Galo Galo Island Morotai. This paper aims to know women’s role for tourism development in Galo-Galo Island, meanwhile Galo-Galo has strong opportunities to be develop in tourism sector. In answer the question, the concept of women participation through Gender and Development Approach by Sofiani is applicable for this case. To complete the process, the writer usequalitative research method by primary and secondary data. The result shows that women play important role in tourism development of Galo Galo Island through involve in the tourism development activities.